2014
DOI: 10.1073/pnas.1323918111
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling reproduction from metabolism extends chronological lifespan in yeast

Abstract: Studies of replicative and chronological lifespan in Saccharomyces cerevisiae have advanced understanding of longevity in all eukaryotes. Chronological lifespan in this species is defined as the agedependent viability of nondividing cells. To date this parameter has only been estimated under calorie restriction, mimicked by starvation. Because postmitotic cells in higher eukaryotes often do not starve, we developed a model yeast system to study cells as they age in the absence of calorie restriction. Yeast cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
51
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 44 publications
(55 citation statements)
references
References 103 publications
3
51
1
Order By: Relevance
“…Planktonic S. cerevisiae cultured in nutrient-limited retentostats retain 80% viability after 22 days,99 and alginate-encapsulated yeast continuously fed ad libitum exhibited >90% viability after almost 3 weeks continuous culture 42. The lower viability reported here may stem from cells being subjected to repeated cycles of feast and famine, each of which F I G U R E 4 Cell escape over time.…”
mentioning
confidence: 74%
See 1 more Smart Citation
“…Planktonic S. cerevisiae cultured in nutrient-limited retentostats retain 80% viability after 22 days,99 and alginate-encapsulated yeast continuously fed ad libitum exhibited >90% viability after almost 3 weeks continuous culture 42. The lower viability reported here may stem from cells being subjected to repeated cycles of feast and famine, each of which F I G U R E 4 Cell escape over time.…”
mentioning
confidence: 74%
“…42 Increased heat resistance displayed by encapsulated cells was once attributed to nutrient deficiency in cells close to the core of the bead, triggering a stress response similar to that observed for cells entering stationary phase. 115 Encapsulated cells are demonstrably heat-shock tolerant ( Figure 6) 42,116 ; others have shown that as much as 25% of this phenotype can be attributed to protection by the matrix itself. 115 Encapsulated cells are demonstrably heat-shock tolerant ( Figure 6) 42,116 ; others have shown that as much as 25% of this phenotype can be attributed to protection by the matrix itself.…”
Section: Cell Escape Increased Over Time Except In Pr Beadsmentioning
confidence: 94%
“…Growth limitation by a nonenergy substrate can be explored, provided that overflow metabolism and reduced efficiency of energy source utilization under such energy excess conditions (90,91) can be prevented. Moreover, cell division can be uncoupled from metabolic activity under glucose excess by continuous cultivation of S. cerevisiae in alginate beads (92).…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…Under these unrestricted nutrient conditions, yeast ceases to divide, remains metabolically active, and exhibits no decline in viability over 2 weeks of continuous culture, a condition that produces proliferation arrest in the presence of nutrients. This effect is totally lost in a rim15 ∆ yeast strain 21. Thus, it appears that when the cell cycle is arrested or compromised, for whatever the reason, CLS increases.…”
Section: The Yeast Cell Cyclementioning
confidence: 95%